2010
DOI: 10.1038/oby.2009.344
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Bioelectrical Impedance Analysis in Adolescents Across Different Ethnic Groups

Abstract: Adolescent obesity is difficult to assess in multi‐ethnic populations using BMI, due to variability in the BMI–fatness relationship. We aimed to describe body composition (BC), and to validate leg–leg bioelectrical impedance analysis (BIA), in adolescents from different ethnic groups using deuterium (D2O) as the reference method. Measurements were made of weight, height, total body water (TBW), and BIA (TANITA TBF‐300) in 110 white, 170 Asian, and 102 black adolescents aged 11–15 years. TBW was converted to le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
78
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(90 citation statements)
references
References 29 publications
8
78
0
3
Order By: Relevance
“…A recent study reported ethnicity as a predictor of TBW with a leg-to-leg BIA in Caucasian, Asian and Afro-American adolescents. 21 However, most studies have found no significant contribution of ethnicity, despite differences in body composition reported in the samples. 22,23 In a study that included New Zealand European, Maori and Pacific Island children; ethnicity was not selected as a predictor in a BIA equation based on isotopic deuterium dilution.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A recent study reported ethnicity as a predictor of TBW with a leg-to-leg BIA in Caucasian, Asian and Afro-American adolescents. 21 However, most studies have found no significant contribution of ethnicity, despite differences in body composition reported in the samples. 22,23 In a study that included New Zealand European, Maori and Pacific Island children; ethnicity was not selected as a predictor in a BIA equation based on isotopic deuterium dilution.…”
Section: Discussionmentioning
confidence: 96%
“…We hypothesized that a specific regression equation might reveal with precision whether individuals from different ethnic groups and regions showed differences in the relationship between body size (BMI) and FM or FFM, as has been shown in other countries. 7 Thus, the objective of this study was to develop equations for bioelectrical impedance and anthropometry based on deuterium oxide dilution to assess body composition in Mexican school children from different geographical regions and ethnic groups.…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of ethnicity into the equation improved the estimation of FFM and TBW in Thai children. Some previous studies have shown that ignoring the ethnicity effect would result in underestimation of FFM by 1.6 kg in black girls (Going et al, 2006), 1.8 kg in Maori and Pacific boys and 1.6 kg in Pacific girls (Sluyter et al, 2009) and 1.5 kg in South Asian girls and 1.3 kg in South Asian boys (Haroun et al, 2010). Several factors can explain the ethnic difference in the relationship between BIA impedance/resistance and TBW/FFM.…”
Section: Development Of Bia Equationsmentioning
confidence: 99%
“…Further, some previous studies have assessed whether ethnicity contributes to the relationship between bioimpedance and body composition in adolescents (Going et al, 2006;Sluyter et al, 2009;Haroun et al, 2010) rather than in children. Therefore, the validity of BIA in a multi-ethnic sample of Asian children is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of relationship between moderate to vigorous physical activity in different environments and fatness could be due to a number of reasons. Firstly, fatness differences exist between white and South Asian children (Deurenberg, Chew & Deurenberg, 2002;Nightingale, Rudnicka, Owen, Cook & Whincup, 2011;Saxena, Ambler, Cole & Majeed, 2004) and the existing criteria for determining adiposity is validated in white populations, providing mean bias in ethnic populations (Haroun et al, 2010). The lack of ethnic specific cutoffs thus might make this challenging (Jebb, Cole, Doman, Murgatroyd & Prentice, 2000;Frisard et al, 2005;Sun et al, 2003).…”
Section: Environment and Fatnessmentioning
confidence: 99%